Autismo : um acontecimento discursivo - Telles, Cynara Maria Andrade (2016)
In this research, we intend to treat autism in a theoretical, clinical and, also, a discursive perspective. We understand it as a discursive event, considering the progresses since the construction of the disorder category assumed by Child Psychiatry M.D. in the 1940’s, an age when childhood mental disorder and other studies related to childhood, arisen and marked all the subsequent course of this theoretical universe. Our research’s object is the autism’s diagnosis, appointments and re-appointments in science, turning the designation process back to the subject with conductions that contrasts the social balance. Further, we first approach the subject, deliberated as abnormal, and the forms of specifying and positioning him. We will do this course, with the purpose of discussing what has been created until we reach the present historical moment: the nosographic name of autism. Therefore, we will turn back the path that science has followed until the current days, with its classificatory conceptions about autism, always prioritizing the path followed by the theoretical constructions and their effects inside medical, psychoanalytic and philosophical knowledge, as, also, autistic child´s itself. And yet, into the (un)knowledge non-experts person, according to legal supplies and their effects on subjects who experience this condition, whether autistics themselves, whether the people whom they live: parents, brethren, educators, professionals. This course aims to confirming autism as a discursive event, as an example, proposed by Foucault. Our intention with such retrieval, considering the positions occupied by this divergent subject, is to discuss the historical, social and political issues that shaped the scenarios and the places by him occupied.